Application of the K-Means Clustering Algorithm in Grouping Regencies/Cities in North Sumatra Province Based on Human Development Index Indicators - Sonia Sihombing; Rahmat W. Sembiring; Eka Irawan (Jurnal Mandiri IT, 2022)
This research aims to group districts/cities in the Province of North Sumatera based on the Human Development Index Indicator. To solve this problem, the researcher uses the K-Means Clustering Algorithm Method. Where the source of research data is collected based on documents describing the Human Development Index produced by the Central Bureau of Statistics. The data used in this researh is the Human Development Index data and the Human Development Index Indicator in 2020. The data will be processed by doing clustering in 3 clusters namely high, medium, and low level of development index. By doing this research, it is expected to be able to the provincial government of North Sumatera regarding the policies that need to be carried out to create equitable development in the Province of North Sumatera, as well as increase the Human Development Index in the Province of North Sumatera.